1D TiO2 Nanostructures Prepared from Seeds Presenting Tailored TiO2 Crystalline Phases and Their Photocatalytic Activity for Escherichia coli in Water. (2nd April 2018) - Cabrera, Julieta; Acosta, Dwight; López, Alcides; Candal, Roberto J.; Marchi, Claudia; García, Pilar; Ríos, Dante; Rodriguez, Juan M.
Abstract : TiO2 nanotubes were synthesized by alkaline hydrothermal treatment of TiO2 nanoparticles with a controlled proportion of anatase and rutile. Tailoring of TiO2 phases was achieved by adjusting the pH and type of acid used in the hydrolysis of titanium isopropoxide (first step in the sol-gel synthesis). The anatase proportion in the precursor nanoparticles was in the 3–100% range. Tube-like nanostructures were obtained with an anatase percentage of 18 or higher while flake-like shapes were obtained when rutile was dominant in the seed. After annealing at 400°C for 2 h, a fraction of nanotubes was conserved in all the samples but, depending on the anatase/rutile ratio in the starting material, spherical and rod-shaped structures were also observed. The photocatalytic activity of 1D nanostructures was evaluated by measuring the deactivation of E. coli in stirred water in the dark and under UV-A/B irradiation. Results show that in addition to the bactericidal activity of TiO2 under UV-A illumination, under dark conditions, the decrease in bacteria viability is ascribed to mechanical stress due to stirring.